Security for Watermark Image - Barbole, Prof. Dr. K. N; Satav, Prof. S.D. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This paper through security will improve the capacity of invisible watermarked data. The watermark image hiding secret bits of information with a digital content as a cover. Most important objectives of information hiding research are that secret information is embedding as much as possible without the perception of the carrier is affected. A hiding information algorithm of LSB bit based on high frequency domain in color image is proposed, which has high imperceptibility and high capacity of information hiding